(untitled) - Raymond Frederic Dasmann (New York, 1984)
The book explores ways to achieve a better balance between human demands and ecological necessities for long-term survival. It provides a text for a course concerned with environmental problems, and natural resource management
Keywords: conservation of nature resources - united states,ecology - united states,human ecology - united states